Denial: The Greatest Barrier to the Opioid Epidemic - Gastala, Nicole (Ann Fam Med, 2017)
“Why can’t you be like my old doctor?” This essay explores my experiences as a new family physician in a rural town endemic with liberal opioid prescribing practices and opioid addiction. I detail my inner turmoil while overcoming resistance to change, the influence of these experiences on my professional growth, and my decision to offer medication-assisted treatment.